Strategi Pembinaan Umat melalui Majelis Taklim dalam Mewujudkan Masyarakat Islami di Desa Baruka Kecamatan Bungin - Sari, Sari; Efendi AS, Arif; Budi, Nurwafiqah Amirah; Saidang; M. Hatta; Suparman (Equilibrium: Jurnal Pendidikan, 2025)
The role of the majelis taklim as a means of community development and a space for social interaction in Baruka Village, Bungin District, which has unique religious dynamics. The purpose of this study is to identify strategies for community development through majelis taklim, analyze congregational participation, and evaluate supporting and inhibiting factors in its implementation. This study uses a descriptive qualitative approach with a case study type, because it is considered relevant to explore socio-religious phenomena in depth and contextually. The technique for determining informants was carried out using purposive sampling, including religious leaders, majelis taklim managers, ustaz/ustazah, and active congregations from various age groups and genders, with the aim of obtaining rich, relevant, and diverse data. Data collection was carried out through participatory observation, in-depth interviews, and documentation of activities, while data analysis used the interactive model of Miles and Huberman which includes data reduction, data presentation, and conclusion drawing, accompanied by triangulation techniques to maintain data validity. The research findings indicate that the religious study groups (Majelis Taklim) in Baruka Village play a significant role in fostering the community through lectures, religious studies, interactive discussions, and the exemplary behavior of religious teachers (Ustaz/Ustazah). This has resulted in increased religious understanding, consistent worship, and strengthened social values ​​and community solidarity. Mothers are the most consistent and productive group, while fathers and adolescents require more adaptive development strategies. Barriers such as limited facilities, varied methods, and fluctuations in congregational attendance still need to be addressed to maximize the role of the religious study groups. This research provides benefits for the development of non-formal education, religious development, and strengthening communities based on Islamic values.